(untitled) (Journal of Astronomy & Earth Sciences Education, 2019)
Young children express interest and understanding about science topics through everyday conversations with parents. Little is known about how much interest preschool-aged children show in astronomy. Using a diary report methodology, we asked parents in three communities in coastal California to keep track of conversations with their three to five-year-old children about nature. The communities varied in demographics, including one community with predominantly European-American families, one community with predominantly Latinx families, and one community with families from a variety of backgrounds. Overall, young children showed interest in astronomy through initiation and engagement in conversations about a variety of astronomical objects and events; this was consistent across gender, age, and community. Across all three communities, conversations about astronomy accounted for approximately 15% of the conversations about nature, ranking in the top three most frequent topics for each group. Children initiated the vast majority of conversations with their parents, including those about astronomy. Within astronomy, children were most interested in the sun, moon, stars, and day or night sky. Thus, while science educators may see astronomy as too complex for young children, children observe and comment on astronomical phenomena as part of their everyday life. Finding ways to support educators and parents in talking with children about these observations may productively build on this early astronomy interest and position children for greater understanding and engagement in this domain.